Phase formation and crystallization of films deposited by pulse laser sputtering of chromium in oxygen atmosphere - Bagmut, A.G.; Grigorov, S.N.; Zhuchkov, V.A.; Kolosov, V.Yu.; Kosevich, V.M.; Nikolaichuk, G.P. (Functional Materials, 2006)
Effects of the substrate temperature Tₛ (20-420 ℃) and the oxygen pressure in the evaporation chamber Р(О₂) (10⁻⁵-10⁻² Torr) on the structure and phase composition of films obtained by pulse laser sputtering of a chromium target have been studied by electron microscopy (using the extinction bending contour technique to analyze the crystal lattice bending). At a fixed Tₛ, the oxygen content in amorphous films increases with increasing Р(О₂), while at a fixed Р(О₂), it decreases with elevating Tₛ. The influence of amorphous matrix composition and thickness t on the structure and morphology of crystals growing under annealing of the films by an electron beam has been studied. The bending of spherulite crystal lattice has been found to decrease with increasing over- stoichiometric Cr concentration in amorphous matrix and with increasing distance up to the center of an zone-axial pattern of the spherulite. At small film thickness t ≤ t ≈ 2.5 to 3 nm, the crystallization is hindered due to dimensional and impurity effect of the amorphous state stabilization.